Longitudinal examination of young married women's fertility and family planning intentions and how they relate to subsequent family planning use in Bihar and Uttar Pradesh India. Issue 7 (21st July 2022) - Speizer, Ilene S; Zavier, A J Francis; Calhoun, Lisa; Nanda, Priya; Saggurti, Niranjan; Hainsworth, Gwyn
Abstract : Objectives: This study examines which fertility and family planning (FP) intentions are related to subsequent FP use in a sample of young, married women in India. Design: We use 3-year longitudinal data from married women ages 15–19 in 2015–2016 (wave 1) who are not using contraception to examine factors associated with any use of FP in 2018–2019 (wave 2). Setting: Data were collected in the states of Bihar and Uttar Pradesh, India. Participants: A representative sample of 4893 young married women ages 15–19 was surveyed in 2015–2016 and 4000 of them were found and interviewed 3 years later. This analysis focused on the 3614 young women who were not using FP at wave 1. Primary outcomes: This study examines FP use at wave 2 as the main outcome variable. Results: Multivariate analyses demonstrated that young women who wanted to delay childbearing three or more years or who did not want any(more) children at wave 1 were more likely to use contraception at wave 2. Additionally, intention to use FP in the next 12 months at wave 1 was significantly associated with FP use at wave 2 whereas unmet need at wave 1 was not significantly related to subsequent use. A combined measure of fertility desires and intention to use FP demonstrated the importance of both measures on subsequent use. Having any children and being pregnant at wave 1 were both related to FP use at wave 2. Conclusions: It is important to reach young, married women prior to a first pregnancy with nuanced messages addressing their fertility and FP intentions. Programmes targeting women at antenatal and postpartum visits are important for young women to help support them to use FP to address their desires to delay or limit future childbearing for the health and well-being of themselves and their children.